Forced Air Precooling Enhanced Storage Quality by Activating the Antioxidant System of Mango Fruits - Jian Li; Yingli Fu; Jiaqi Yan; Huanlu Song; Weibo Jiang (Journal of Food Quality)
Effects of forced air precooling on storage quality and physiological metabolism of mangoes were evaluated in this study. Mango fruits were forced air precooled for 30 min at 0°C and then stored at 13°C. Control fruits were stored at 13°C directly. Results showed that forced air precooling treatment maintained fruit firmness, inhibited fruit peel coloration, retarded hydrolysis of polysaccharide to soluble sugar, and decreased fruit decay during storage. Biochemical studies revealed that precooling treatment could eliminate reactive oxygen species (ROS) effects by enhancing related antioxidant enzyme activities, such as superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), glutathione reductase (GR), and polyphenoloxidase (PPO). They all contributed to the delay of mango fruit ripening and senescence in storage. These results indicate that forced air precooling treatment could maintain mango fruit quality by enhancing antioxidant activity and delaying fruit ripening.